Sustainable Development - Relationships to Culture, Knowledge and Ethics - Parodi, OliverAyestaran, IgnacioBanse, Gerhard [Hrsg.] (Karlsruher Studien Technik und Kultur / Hrsg.: G. Banse, A. Böhn, A. Grunwald, K. Möser, M. Pfadenhauer, 2011)
The emergence of a global and technological world and its accelerating, dissemination before the beginning of the 21st century does not only give rise to technological, economic, social, environmental, political, and educational tasks. Significant philosophical questions, epistemic reflections, and cultural debates result. The aim of this book is to provide information about epistemic, ethical, and cultural implications of sustainable development on an interdisciplinary and international level.